2013
DOI: 10.12720/joams.1.4.395-400
|View full text |Cite
|
Sign up to set email alerts
|

Complex Risk Analysis of Natural Hazards through Fuzzy Logic

Abstract: The paper presents a fuzzy logic approach to complex risk analysis in regard to each of the natural hazards for a given monitoring region. This approach is based on the available statistical data and the expert knowledge. The calculations of the complex risk are done for five regions in SW Bulgaria (Dupnitsa, Blagoevgrad, Simitli, Kresna and Sandanski). The proposed risk analysis is envisaged to be implemented as a part of a Web information system for risk management of natural disasters.  Index Terms-risk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…In this relation and in case of shortage of data we applied fuzzy logic (Zimmerman, 1996) to make a complex assessment of multiple natural hazard level (Zlateva and Velev, 2013) and adding the time component (duration and total amount of rain). We designed fuzzy logic model with three inputs as follow: input 1 (with the highest importance for common hazard level) the total amount of intensive rain; input 2 (with moderate importance for common hazard level)the multiple hazard level and input 3 (with less importance for common hazard level) the rain duration.…”
Section: Methodsmentioning
confidence: 99%
“…In this relation and in case of shortage of data we applied fuzzy logic (Zimmerman, 1996) to make a complex assessment of multiple natural hazard level (Zlateva and Velev, 2013) and adding the time component (duration and total amount of rain). We designed fuzzy logic model with three inputs as follow: input 1 (with the highest importance for common hazard level) the total amount of intensive rain; input 2 (with moderate importance for common hazard level)the multiple hazard level and input 3 (with less importance for common hazard level) the rain duration.…”
Section: Methodsmentioning
confidence: 99%
“…To address question (i) from the perspective of a disaster risk analysis, all potential natural disasters in the research region must be identified and considered [117][118][119][120]. The particular context of the research region and the study's goal determine which risks are important.…”
Section: Risk Analysismentioning
confidence: 99%
“…Afet Sonrası Yönetim Sisteminin temel amacı kurtarma kaynaklarını adil ve verimli bir şekilde yönetmektir. Literatürde afet yönetim sistemlerinde kullanılan yöntemlerden biri olduğu için karar destek sistemi olarak bulanık mantık tercih edilmiştir [18][19][20]. Kullanılan bulanık temelli karar destek sistemi Şekil 6'da verilmektedir.…”
Section: Bulanık Mantık Tabanlı Karar Destek Sistemiunclassified